Disinfected Smart Voting System using Aadhaar as UID - et. al., Praveen Kumar K, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The election is the central criterion in every country to choose their best leader in society. Meanwhile, the technologies used in the time of the election are also an important thing to maintain the economic balance, security for the voting, and safety of the voter's health as well. Currently in India, we are going to use the EVM machines to cast the votes, this method of manually maintaining the process of the election is a tedious task, for this, we are going to introduce a system of maintaining the election procedure electronically by using the IoT device with Aadhaar linking called Biometric with automatic sanitization of the voters during the time of the election with giving the security to the casted votes in the central hub safely. The method of linking the Aadhaar data to the election is to avoid the proxy voters during the time of the election, introducing the IoT device of the automated sanitizing device in the polling station may help to avoid the spreading of the pandemic from the biometric device. The maintaining of the security of the votes carried out by using the MAC address.